Lithium-carbon composite material, negative pole piece and secondary battery

By introducing a protective layer and a porous carbon layer into the lithium carbon composite material and optimizing its structural parameters, the dendrite growth, volume expansion and side reaction problems of lithium carbon composite material during charging and discharging are solved, and the excellent cycle performance and safety performance of the secondary battery are achieved.

CN119673996APending Publication Date: 2025-03-21ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411808690.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the charging and discharging process of lithium carbon composites, there are problems with dendrite growth, volume expansion and side reactions with the electrolyte, resulting in damage to the electrode structure and affecting the cycle life and safety of the battery.

Method used

A lithium carbon composite material is designed, including a lithium metal core, a protective layer coated on the surface of the lithium metal core, and a porous carbon layer coated on the surface of the protective layer. The protective layer consists of organic and inorganic cladding materials, the porous carbon layer has holes on the surface, and there is a gap between the protective layer and the porous carbon layer, satisfying a specific elastic modulus and thickness relationship.

Benefits of technology

Through this design, lithium carbon composite materials show excellent circulation performance, safety performance and high Coulomb efficiency in secondary batteries, effectively alleviating the problems of dendrites' growth and volume expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179970030000121
    Figure BDA0005179970030000121
  • Figure BDA0005179970030000131
    Figure BDA0005179970030000131
  • Figure BDA0005179970030000141
    Figure BDA0005179970030000141
Patent Text Reader

Abstract

The invention discloses a lithium-carbon composite material, a negative pole piece and a secondary battery, and belongs to the technical field of batteries. The lithium-carbon composite material provided by the invention comprises a lithium metal core, a protective layer coated on the surface of the lithium metal core and a porous carbon layer coated on the surface of the protective layer, holes are formed in the surface of the porous carbon layer, a gap is formed between the coating layer and the porous carbon layer, and the lithium-carbon composite material meets the specific relational expression: E * (d2 / d1) 3 / 2 / 10 is greater than or equal to 1 and less than or equal to 7, when the obtained lithium-carbon composite material is applied to a secondary battery as a negative electrode material, the obtained secondary battery has excellent cycle performance, safety performance and relatively high coulombic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a lithium-carbon composite material, a negative electrode sheet and a secondary battery. Background Art

[0002] With the rapid development of portable electronic devices, electric vehicles and energy storage systems, higher requirements are placed on the performance of lithium-ion batteries. As anode materials for lithium-ion batteries, lithium-carbon composites are considered to be one of the most promising anode materials for the next generation of high-energy-density lithium-ion batteries due to their extremely high theoretical specific capacity (3860mAh / g) and lowest electrochemical potential (-3.04V vs. standard hydrogen electrode). However, during the charge and discharge process, lithium-carbon composites have serious problems such as dendrite growth, volume expansion, and continuous side reactions with the electrolyte, which lead to the destruction of the electrode structure and affect the cycle life and safety of the battery, which greatly limits its practical application. Summary of the invention

[0003] The purpose of this application is to solve the technical problem in the prior art that the performance of lithium metal negative electrodes needs to be improved, and proposes a lithium-carbon composite material, a negative electrode sheet and a secondary battery.

[0004] To achieve the above-mentioned object, in a first aspect of the present application, a lithium-carbon composite material is provided, wherein the lithium-carbon composite material comprises a lithium metal core, a protective layer coated on the surface of the lithium metal core, and a porous carbon layer coated on the surface of the protective layer;

[0005] The porous carbon layer has holes on its surface, and there is a gap between the protective layer and the porous carbon layer;

[0006] The protective layer comprises an organic coating material and an inorganic coating material, and the mass ratio of the organic coating material to the inorganic coating material is 1:(3-7);

[0007] The lithium-carbon composite material satisfies: 1≤A≤7,

[0008] Where A = E*(d2 / d1)^ 3 / 2 / 10;

[0009] E PGa is the elastic modulus of the protective layer;

[0010] d1 nm is the thickness of the protective layer;

[0011] d2 nm is the thickness of the porous carbon layer.

[0012] As an embodiment of the present application, the elastic modulus E of the protective layer is 9-12PGa.

[0013] As an embodiment of the present application, the thickness d1 of the protective layer is 200-600 nm.

[0014] As an embodiment of the present application, the thickness d2 of the porous carbon layer is 400-800 nm.

[0015] As an embodiment of the present application, based on the total mass of the lithium-carbon composite material, the mass percentage of the lithium metal core is 40-70%.

[0016] As an embodiment of the present application, the volume percentage of the gap is 10-50% based on the sum of the volumes of the protection layer and the gap.

[0017] As an embodiment of the present application, the porosity of the porous carbon layer is 20-40%.

[0018] As an embodiment of the present application, the organic coating material includes at least one of polyethylene glycol diacrylate, polypropylene, polydimethylsiloxane, polyethylene glycol, polyvinylidene fluoride, polyphthalamide, and polyacrylic acid.

[0019] As an embodiment of the present application, the inorganic coating material includes at least one of lithium phosphate, lithium fluoride, silicon dioxide, aluminum oxide, molybdenum disulfide, hexagonal boron nitride, carbon paper, and graphite.

[0020] In a second aspect of the present application, the present application provides a negative electrode plate, which includes a negative electrode collector and a negative electrode active material layer arranged on at least one side of the negative electrode collector, and the negative electrode active material layer includes the lithium-carbon composite material described in the present application.

[0021] In a third aspect of the present application, the present application provides a secondary battery, wherein the secondary battery comprises the negative electrode plate described in the present application.

[0022] Compared with the prior art, the beneficial effects of this application are:

[0023] The present application provides a lithium-carbon composite material comprising a lithium metal core, a protective layer coated on the surface of the lithium metal core, and a porous carbon layer coated on the surface of the protective layer, wherein the surface of the porous carbon layer has holes, and there is a gap between the coating layer and the porous carbon layer, and the lithium-carbon composite material satisfies a specific relationship: 1≤E*(d2 / d1)^ 3 / 2 / 10≤7, when the obtained lithium-carbon composite material is used as a negative electrode material in a secondary battery, the obtained secondary battery has excellent cycle performance, safety performance and high coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of the structure of the lithium-carbon composite material for this application:

[0025] 1-porous carbon layer, 2-protective layer, 3-metal lithium, 4-gap, 5-hole. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0027] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0028] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0029] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0030] In one embodiment of the present application, the present application proposes a lithium-carbon composite material, wherein the lithium-carbon composite material includes a lithium metal core, a protective layer coated on the surface of the lithium metal core, and a porous carbon layer coated on the surface of the protective layer;

[0031] The porous carbon layer has holes on its surface, and there is a gap between the protective layer and the porous carbon layer;

[0032] The protective layer comprises an organic coating material and an inorganic coating material, and the mass ratio of the organic coating material to the inorganic coating material is 1:(3-7);

[0033] The lithium-carbon composite material satisfies: 1≤A≤7,

[0034] Where A = E*(d2 / d1)^ 3 / 2 / 10;

[0035] E PGa is the elastic modulus of the protective layer;

[0036] d1 nm is the thickness of the protective layer;

[0037] d2 nm is the thickness of the porous carbon layer.

[0038] The present application provides a lithium-carbon composite material comprising a lithium metal core, a protective layer coated on the surface of the lithium metal core, and a porous carbon layer coated on the surface of the protective layer, wherein the surface of the porous carbon layer has holes, and there is a gap between the coating layer and the porous carbon layer, and the lithium-carbon composite material satisfies a specific relationship: 1≤E*(d2 / d1)^ 3 / 2 / 10≤7, when the obtained lithium-carbon composite material is used as a negative electrode material in a secondary battery, the obtained secondary battery has excellent cycle performance, safety performance and high coulombic efficiency.

[0039] Specifically, the present application sets a protective layer on the surface of the lithium metal core, and defines that the coating layer includes an organic coating material and an inorganic coating material within a specific mass ratio range. On the one hand, the introduced protective layer makes the lithium-carbon composite material have good chemical stability, which can effectively prevent the electrolyte from contacting with metallic lithium during the cycle to produce side reactions; on the other hand, the introduced protective layer can also make the lithium-carbon composite material have good lithium ion conductivity, which can ensure that lithium ions are uniformly deposited on the surface of metallic lithium to avoid the growth of lithium dendrites; on the third hand, the protective layer of the present application also has high elasticity and density, which can adapt to the volume expansion changes during the charging and discharging process, and can effectively avoid the cracking and shedding of the protective layer, thereby further improving the stability of the lithium-carbon composite material. In addition, the present application sets a porous carbon layer with holes outside the protective layer, and further defines that there is a gap between the protective layer and the porous carbon layer. On the one hand, the introduction of the porous carbon layer with holes can provide a convenient channel for the transmission of lithium ions and improve the lithium insertion rate; on the other hand, the gap between the protective layer and the porous carbon layer provides space for the expansion of metallic lithium during the charging and discharging process, further alleviating the volume expansion of the material when lithium is inserted. At the same time, the present application further defines that the lithium-carbon composite material satisfies 1≤E*(d2 / d1)^ 3 / 2 / 10≤7, which can effectively balance the thickness relationship between the protective layer and the porous carbon layer, thereby achieving good comprehensive performance.

[0040] It should be noted that the masses of the organic coating material and the inorganic coating material in the protective layer can be tested by SEM, EDS, and TEM, and after the masses of the two are obtained, the mass ratio of the two can be calculated.

[0041] Exemplarily, the mass ratio of the organic coating material to the inorganic coating material may be any point value or any range value between 1:(3-7), such as 1:3, 1:4, 1:5, 1:6, 1:7, etc.

[0042] The present application has found that if there is too much organic coating material in the protective layer, although the elastic modulus of the prepared protective layer will be higher, the lithium ion conductivity will be lower, which will affect the uniform transport during the cycle; if there is too much inorganic coating material in the protective layer, although the conductivity of the prepared protective layer will be higher, the elasticity will be poor, and it will be impossible to achieve dense protection for metallic lithium, and it will be difficult to shield the corrosion of the electrolyte when it is prepared into a secondary battery, and it will be impossible to adapt to changes in volume expansion; therefore, when the mass ratio of the organic coating material and the inorganic coating material is further selected within the range given in the present application, the lithium ion transmission rate and the elasticity of the protective layer can be taken into account, thereby achieving the excellent comprehensive performance of the secondary battery prepared subsequently.

[0043] Exemplarily, A may be any point value or any range of two points between 1 and 7, such as 1, 2, 3, 4, 5, 6, 7, etc.

[0044] In one embodiment, 2.1≤A≤4.6. For example, it can be 2.1, 2.3, 2.5, 2.7, 2.9, 3.1, 3.3, 3.5, 3.7, 3.9, 4.1, 4.3, 4.5, 4.6, etc. The present application study found that when 2.1≤A≤4.6 is further selected, the complementary relationship between the protective layer and the porous carbon layer is better, so that when the lithium-carbon composite material is used as a negative electrode material in the preparation of a secondary battery, the obtained secondary battery has better cycle performance and safety performance; it avoids the increase in the thickness of the protective layer and the porous carbon layer, which increases the transmission path of lithium ions, or the reduction in thickness, which makes it impossible to restrain the expansion of lithium insertion in the material and causes the membrane layer to crack.

[0045] In one embodiment, the elastic modulus E of the protective layer is 9-12PGa.

[0046] It should be noted that the elastic modulus of the protective layer is obtained by atomic force microscope (AFM) testing.

[0047] Exemplarily, the elastic modulus E of the protective layer may be any value between 9-12PGa or any two points in the range, such as 9PGa, 9.5PGa, 10PGa, 10.5PGa, 11PGa, 11.5PGa, 12PGa, etc.

[0048] In one embodiment, the elastic modulus E of the protective layer is 10-11PGa, for example, 10PGa, 10.1PGa, 10.2PGa, 10.3PGa, 10.4PGa, 10.5PGa, 10.6PGa, 10.7PGa, 10.8PGa, 10.9PGa, 11PGa, etc.

[0049] The present application found that the elastic modulus of the protective layer within a certain range can effectively suppress the volume expansion change during the cycle, achieving a good stabilizing structure, thereby improving the cycle performance and safety performance of the secondary battery prepared subsequently. When the elastic modulus E of the protective layer is further selected to be 9-12PGa, especially 10-11PGa, the comprehensive performance of the secondary battery obtained is better.

[0050] In one embodiment, the thickness d1 of the protective layer is 200-600 nm.

[0051] It should be noted that the thickness d1 of the protective layer is obtained by transmission electron microscopy (TEM) testing.

[0052] Exemplarily, the thickness d1 of the protective layer may be any point value or any two point range value between 200-600 nm, for example, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, etc.

[0053] In one embodiment, the thickness d1 of the protective layer is 220-300 nm, for example, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm, etc.

[0054] The present application study found that the thickness of the protective layer will affect both the lithium ion deintercalation rate and the structural stability of the material. When the thickness d1 of the protective layer is further selected to be 200-600nm, especially 220-300nm, the obtained lithium-carbon composite material is used in the preparation of secondary batteries, and the comprehensive performance of the obtained secondary batteries is better.

[0055] In one embodiment, the thickness d2 of the porous carbon layer is 400-800 nm.

[0056] It should be noted that the thickness d2 of the porous carbon layer is obtained by transmission electron microscopy (TEM) testing.

[0057] Exemplarily, the thickness d2 of the porous carbon layer may be any point value or any two point range values ​​between 400-800 nm, for example, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, etc.

[0058] In one embodiment, the thickness d2 of the porous carbon layer is 500-600 nm, for example, 500 nm, 510 nm, 520 nm, 530 nm, 540 nm, 550 nm, 560 nm, 570 nm, 580 nm, 590 nm, 600 nm, etc.

[0059] The present application has found that when the thickness of the porous carbon layer is within the above range, it can suppress volume expansion while being more conducive to structural stability, thereby achieving excellent comprehensive performance of the secondary battery prepared subsequently.

[0060] In one embodiment, based on the total mass of the lithium-carbon composite material, the mass percentage of the lithium metal core is 40-70%.

[0061] It should be noted that the mass percentage of the lithium metal core based on the total mass of the lithium-carbon composite material is obtained by flame atomic absorption spectrometry testing and characterization. Based on the principle of atomic absorption spectroscopy, the content of metallic lithium is determined by measuring the degree of absorption of light of a specific wavelength by metallic lithium atoms in the sample.

[0062] Exemplarily, based on the total mass of the lithium-carbon composite material, the mass percentage of the lithium metal core can be any point value between 40-70% or any two point range values, such as 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc.

[0063] The present application has found that selecting the mass percentage of the lithium metal core in the lithium-carbon composite material within the above range can provide sufficient lithium metal and improve the coulombic efficiency and energy density of the secondary battery prepared subsequently.

[0064] In one embodiment, based on the sum of the volumes of the protection layer and the gap, the volume percentage of the gap is 10-50%.

[0065] It should be noted that the volume percentage of the gap is calculated based on the sum of the volumes of the protective layer and the gap and is obtained through transmission electron microscopy (TEM) testing and characterization.

[0066] Exemplarily, based on the sum of the volumes of the protective layer and the gap, the volume percentage of the gap can be any point value between 10-50% or any two point range values, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0067] The present application has found that selecting a gap volume percentage within the above range, which is calculated as the sum of the volumes of the protective layer and the gap, can provide sufficient space for the volume expansion of metallic lithium during the charge and discharge process, thereby improving the cycle stability of the material, while also avoiding the problem of a longer transmission path due to an excessively large gap.

[0068] In one embodiment, the porosity of the porous carbon layer is 20-40%.

[0069] It should be noted that the method for testing the porosity of the porous carbon layer is to use nitrogen as the adsorption gas and calculate the porosity of the material by measuring the adsorption amount of the material under a certain pressure.

[0070] Exemplarily, the porosity of the porous carbon layer may be any point value between 20-40% or any two points in the range, such as 20%, 25%, 30%, 35%, 40%, etc.

[0071] The present application study found that the porosity of the porous carbon layer affects the transmission rate of lithium ions and also affects the structural stability of the lithium-carbon composite material. When the porosity of the porous carbon layer is further selected to be within the above range, the obtained lithium-carbon composite material is used as a negative electrode material in the preparation of a secondary battery, and the overall performance of the obtained secondary battery is better.

[0072] In one embodiment, the organic coating material includes at least one of polyethylene glycol diacrylate, polypropylene, polydimethylsiloxane, polyethylene glycol, polyvinylidene fluoride, polyphthalamide, and polyacrylic acid.

[0073] In one embodiment, the organic coating material is polyethylene glycol diacrylate.

[0074] In one embodiment, the inorganic coating material includes at least one of lithium phosphate, lithium fluoride, silicon dioxide, aluminum oxide, molybdenum disulfide, hexagonal boron nitride, carbon paper, and graphite.

[0075] In one embodiment, the inorganic coating material is at least one of lithium phosphate and lithium fluoride.

[0076] The present application has studied and found that when the above-mentioned organic coating materials and inorganic coating materials are selected, when the obtained products are used in the preparation of secondary batteries, the comprehensive performance of the obtained secondary batteries is more excellent.

[0077] In one embodiment, the method for preparing the lithium-carbon composite material comprises the following steps:

[0078] (1) adding an organic coating material and an inorganic coating material to an organic solvent and stirring to mix them evenly, then adding a curing agent and continuing to stir to obtain a mixed solution A; then adding lithium metal particles to the mixed solution A, stirring, and filtering, collecting the solid and drying it under ultraviolet light at (-50)-(-30)° C. to obtain metallic lithium coated with a protective layer;

[0079] (2) The metallic lithium and graphite coated with the protective layer are mixed evenly, and then a binder is added to mix, and then N,N-dimethylformamide is added to ball mill. After the ball milling, water vapor is introduced to react, and after the reaction is completed, freeze-drying is performed to obtain a lithium-carbon composite material.

[0080] In one embodiment, in step (1), the organic solvent includes at least one of ethylene glycol dimethyl ether, ethanol, methanol, and N,N-dimethylformamide.

[0081] In one embodiment, in step (1), the curing agent includes 2-hydroxy-2-methylpropiophenone.

[0082] In one embodiment, in step (2), the binder includes at least one of polyvinylidene fluoride, carboxymethyl cellulose, and styrene-butadiene rubber.

[0083] In the preparation method of the lithium-carbon composite material provided by the present application, by first placing it under low temperature and ultraviolet light for drying, the high energy of the ultraviolet light can be effectively utilized to allow the protective layer to grow closely on the surface of the metal lithium, and at the same time, the unsaturated bond polymerization of the organic coating can be quickly stimulated, the polymerization reaction time is shortened, and the production efficiency is improved. In addition, after the protective layer is formed, ball milling is performed, and after the ball milling is completed, water vapor is introduced for reaction, which can effectively form a porous carbon layer, and there is a gap between the porous carbon layer and the protective layer.

[0084] In one embodiment, in the step (2), the mass percentage of polyvinylidene fluoride is 3-5% based on the total mass of the metallic lithium and graphite coated by the protective layer.

[0085] In one embodiment, in the step (2), the ball milling time is 50-70 min.

[0086] In one embodiment, in the step (2), the time for introducing water vapor to react after the ball milling is 10-20 minutes.

[0087] In one embodiment of the present application, the present application provides a negative electrode plate, which includes a negative electrode collector and a negative electrode active material layer arranged on at least one side of the negative electrode collector, and the negative electrode active material layer includes the lithium-carbon composite material described in the present application.

[0088] In one embodiment, in the negative electrode active material layer, the mass percentage of the lithium-carbon composite material is 95-99%.

[0089] In one embodiment of the present application, the present application provides a secondary battery, and the secondary battery includes the negative electrode plate described in the present application.

[0090] In one embodiment, the secondary battery further includes a positive electrode plate, a separator and an electrolyte.

[0091] In one embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector; the positive electrode active material layer includes a positive electrode active material. The present application has no limitation on the positive electrode active material, and any known positive electrode active material can be used.

[0092] Exemplarily, the positive electrode active material includes at least one of lithium cobalt oxide, ternary materials, and lithium-rich materials.

[0093] In one embodiment, the electrolyte further comprises an organic solvent and a lithium salt. The present application has no limitation on the organic solvent and the lithium salt in the electrolyte, and any known organic solvent and lithium salt can be used.

[0094] Exemplarily, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate; the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

[0095] In one embodiment, the separator of the secondary battery is disposed between the positive electrode and the negative electrode.

[0096] The present application has no limitation on the diaphragm, and any known diaphragm may be used.

[0097] Exemplarily, the diaphragm includes any one of a polyethylene diaphragm, a polypropylene diaphragm, a polyvinylidene fluoride diaphragm, and a multi-layer composite film.

[0098] Example 1

[0099] The present application provides a lithium-carbon composite material, a negative electrode sheet and a secondary battery. The preparation method of the lithium-carbon composite material, the negative electrode sheet and the secondary battery comprises the following steps:

[0100] (1) Preparation of lithium-carbon composite materials

[0101] S1. Take 1 part of organic coating material (polyvinylidene fluoride) and 4 parts of inorganic coating material (lithium phosphate) and add them to 6 parts of ethylene glycol dimethyl ether and stir for 60 minutes, then add 0.6 parts of 2-hydroxy-2-methylpropiophenone and continue stirring for 20 minutes to obtain a mixed solution A; then add 8 parts of lithium metal particles to the mixed solution A, stir for 5 minutes and filter, collect the solid and place it under ultraviolet light at (-40)°C to dry for 10 minutes to obtain metallic lithium coated with a protective layer;

[0102] S2, 1 part of metallic lithium coated with a protective layer and 3 parts of graphite are mixed evenly, and then polyvinylidene fluoride (the mass of polyvinylidene fluoride accounts for 4% of the total mass of metallic lithium coated with a protective layer and graphite) is added to mix, and then 3 parts of N, N-dimethylformamide are added to ball mill for 60 minutes, and water vapor is introduced to react for 15 minutes after the ball milling. After the reaction is completed, freeze-drying (drying temperature is -20°C, time is 24 hours) to obtain a lithium-carbon composite material;

[0103] The structural schematic diagram of the obtained lithium-carbon composite material is shown in Figure 1 As shown;

[0104] (2) Preparation of negative electrode sheet

[0105] The lithium-carbon composite material prepared in step (1), a conductive agent (a mixture of ultrafine carbon powder and carbon nanotubes in a mass ratio of 0.45:0.05), and a binder (a mixture of styrene-butadiene rubber and lithium polyacrylate in a mass ratio of 0.5:1.8) are fully stirred in deionized water at a mass ratio of 97.7:1.1:1.2, and then coated on a copper foil, and dried, rolled, and slit to obtain a negative electrode sheet;

[0106] (3) Preparation of positive electrode sheet

[0107] The positive electrode material lithium cobalt oxide, conductive agent (acetylene black), conductive agent (carbon nanotubes), and binder (polyvinylidene fluoride) are fully stirred and mixed in N-methylpyrrolidone at a mass ratio of 97.6:0.5:0.6:1.3, and then coated on aluminum foil, and dried, rolled, and slit to obtain a positive electrode sheet;

[0108] (4) Preparation of electrolyte

[0109] Ethylene carbonate, propylene carbonate, diethyl carbonate and propyl propionate are mixed in a volume ratio of 1.2:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte;

[0110] (5) Preparation of diaphragm

[0111] The ceramic mixture is coated on the surface of PE to obtain a diaphragm;

[0112] (6) Preparation of secondary batteries

[0113] The prepared positive electrode sheet, negative electrode sheet, separator and other battery components are assembled, and a secondary battery is obtained through processes such as shaping, baking, packaging, liquid injection, formation, and capacity division.

[0114] Embodiment 2-4

[0115] The embodiment of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the ultraviolet irradiation time is adjusted to achieve the parameters in Table 1.

[0116] Embodiment 5-7

[0117] The embodiment of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the amount of the protective layer raw material added is adjusted to achieve the parameters in Table 1.

[0118] Embodiment 8-10

[0119] The embodiment of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the amount of porous carbon layer raw material added is adjusted to achieve the parameters in Table 1.

[0120] Embodiment 11

[0121] The embodiment of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the ball milling time is adjusted to achieve the parameters in Table 1.

[0122] Examples 12-13

[0123] The embodiment of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the amount of metallic lithium added is adjusted to achieve the parameters in Table 1.

[0124] Examples 14-15

[0125] The embodiment of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the parameters in the preparation process are adjusted to achieve the parameters in Table 1.

[0126] Examples 16-17

[0127] The embodiment of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the freeze-drying time is adjusted to achieve the parameters in Table 1.

[0128] Examples 18-19

[0129] The embodiment of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the mass ratio of the organic coating material and the inorganic coating material of the protective layer is adjusted to achieve the parameters in Table 1.

[0130] Examples 20-21

[0131] The embodiment of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the types of organic coating materials and inorganic coating materials of the protective layer are adjusted to achieve the parameters in Table 1.

[0132] Comparative Example 1

[0133] The comparative example of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that no protective layer is introduced to achieve the parameters in Table 1.

[0134] Comparative Example 2

[0135] The comparative example of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that no porous carbon layer is introduced to achieve the parameters in Table 1.

[0136] Comparative Examples 3-4

[0137] The comparative example of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the mass ratio of the organic coating material and the inorganic coating material of the protective layer is adjusted to achieve the parameters in Table 1.

[0138] Comparative Examples 5-6

[0139] The comparative example of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the addition ratio of the organic coating material and the inorganic coating material is adjusted to achieve the parameters in Table 1.

[0140] Comparative Example 7

[0141] The comparative example of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the preparation process is adjusted to achieve the parameters in Table 1.

[0142] Comparative Example 8

[0143] The comparative example of the present application provides a lithium-carbon composite material, a negative electrode plate and a secondary battery. The only difference from Example 1 is that the raw materials of the porous carbon layer are adjusted to achieve the parameters in Table 1.

[0144] The elastic modulus E of the protective layer in the lithium-carbon composite material, the thickness d1 of the protective layer, the thickness d2 of the porous carbon layer, A, the mass percentage Y1 of the lithium metal core based on the total mass of the lithium-carbon composite material, the volume percentage V1 of the gap based on the sum of the volume of the protective layer and the gap, the porosity P of the porous carbon layer, the organic coating material, the inorganic coating material, and the mass ratio M1 of the organic coating material and the inorganic protective material are shown in Table 1;

[0145] Table 1

[0146]

[0147]

[0148] The cycle performance and coulombic efficiency of the secondary batteries prepared in the examples and comparative examples are shown in Table 2; wherein the test method comprises the following steps:

[0149] 1) Cycle test: At 25℃, perform cycle test according to the following method, charging mode: 2.8C CC to 4.27V, 2C CC to 4.35V, CV to 1.8C, 1.8C CC to 4.45V, CV to 1.5C, 1.5C CC to 4.5V, CV to 1.2C, 1.2C CC to 4.55V, CV to 0.25C; discharge mode: 0.7C DC to 3.0V;

[0150] 500-week Fading = discharge capacity of the 500th week / discharge capacity of the 1st week * 100%;

[0151] 500-week Swelling = 500th week full-charge thickness / initial half-charge thickness * 100%;

[0152] The battery thickness test uses a 600PPG thickness gauge;

[0153] 2) Coulomb efficiency test: At 25℃, perform cycle test according to the following method, charging mode: 2.8C CC to 4.27V, 2C CC to 4.35V, CV to 1.8C, 1.8C CC to 4.45V, CV to 1.5C, 1.5C CC to4.5V, CV to 1.2C, 1.2C CC to 4.55V, CV to 0.25C; discharge mode: 0.7C DC to3.0V;

[0154] 300-cycle coulomb efficiency = 300th-cycle discharge capacity / 300th-cycle charge capacity * 100%;

[0155] Table 2

[0156]

[0157]

[0158] It can be seen from Table 2 that when the lithium-carbon composite material prepared by the method provided by the present application is used as a negative electrode material in the preparation of a secondary battery, the obtained secondary battery has excellent cycle performance and high coulombic efficiency; specifically, the obtained secondary battery has a Fading of more than 86.49% at 25°C for 500 weeks, a Swelling of less than 13.91% at 25°C for 500 weeks, and a coulombic efficiency of more than 98.4% at 300 weeks;

[0159] It can be seen from Examples 1-21 and Comparative Examples 1-2 that when a protective layer or a porous carbon layer is not introduced into the lithium-carbon composite material, the cycle performance and coulombic efficiency of the obtained secondary battery show a significant downward trend; it can be seen from Example 1, Examples 18-19 and Comparative Examples 3-4 that the mass ratio of the organic coating material and the inorganic coating material in the protective layer will also affect the performance of the product. When the mass ratio of the organic coating material and the inorganic coating material in Comparative Examples 3-4 is not within the range given in the present application, the comprehensive performance of the obtained secondary battery is also significantly reduced; it can be seen from Examples 1-21 and Comparative Examples 5-6 that when the lithium-carbon composite material does not satisfy 1≤E*(d2 / d1)^ 3 / 2 When / 10≤7, the comprehensive performance of the obtained secondary battery is significantly reduced.

[0160] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A lithium-carbon composite material, characterized in that: The lithium-carbon composite material comprises a lithium metal core, a protective layer coated on the surface of the lithium metal core, and a porous carbon layer coated on the surface of the protective layer; The porous carbon layer has holes on its surface, and there is a gap between the protective layer and the porous carbon layer; The protective layer comprises an organic coating material and an inorganic coating material, and the mass ratio of the organic coating material to the inorganic coating material is 1:(3-7); The lithium-carbon composite material satisfies: 1≤A≤7, Where A = E*(d2 / d1)^ 3 / 2 / 10; E PGa is the elastic modulus of the protective layer; d1 nm is the thickness of the protective layer; d2 nm is the thickness of the porous carbon layer.

2. The lithium-carbon composite material according to claim 1, characterized in that The elastic modulus E of the protective layer is 9-12PGa.

3. The lithium-carbon composite material according to claim 1, characterized in that The thickness d1 of the protective layer is 200-600 nm.

4. The lithium-carbon composite material according to claim 1, characterized in that The thickness d2 of the porous carbon layer is 400-800 nm.

5. The lithium-carbon composite material according to claim 1, characterized in that Based on the total mass of the lithium-carbon composite material, the mass percentage of the lithium metal core is 40-70%.

6. The lithium-carbon composite material according to claim 1, characterized in that The volume percentage of the gap is 10-50% based on the sum of the volume of the protective layer and the gap.

7. The lithium-carbon composite material according to claim 1, characterized in that The porosity of the porous carbon layer is 20-40%.

8. The lithium-carbon composite material according to claim 1, characterized in that The organic coating material includes at least one of polyethylene glycol diacrylate, polypropylene, polydimethylsiloxane, polyethylene glycol, polyvinylidene fluoride, polyphthalamide, and polyacrylic acid; And / or, the inorganic coating material includes at least one of lithium phosphate, lithium fluoride, silicon dioxide, aluminum oxide, molybdenum disulfide, hexagonal boron nitride, carbon paper, and graphite.

9. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises the lithium-carbon composite material according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet as claimed in claim 9.